Peranan Agama Sebagai Sistem Sosial Masyarakat Beragama (Studi Teori Sistem Niklas Luhman) - Nurhanipah Harahap Hanipah (ZARATHUSTRA (Jurnal Sosiologi dan Filsafat), 2023)
This paper is a philosophical study that discusses one of the theories of sociologist figures developed by Niklas Luhman regarding system theory that is applied and becomes the theme of discussion in this research, namely religion as a social system of religious communities. Religion as a communication system among the people plays an important role, religion was created by Allah, various types of religions throughout the world with the aim that fellow religious communities respect and love one another. The method used in this research is library research by collecting data from various literature. The results of the research that I want to discuss here are to show and explain that it is so important to build a communication as a social system in a religious society. In an important sense, that the role of religion in the public communication system is as a tool for organizing all things that are carried out in the realm of the social sphere. It is clear that if there is no community religion, it will not be possible to build a well-developed religious community communication